2019
DOI: 10.14202/vetworld.2019.1140-1149
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, detection of virulence genes, antibiotic resistance genes, plasmid profile, and molecular typing among Vibrio parahaemolyticus isolated in Malaysian seawater from recreational beaches and fish

Abstract: Background and Aim: Despite the importance of the global emergence of Vibrio parahaemolyticus infections worldwide, there has been scanty information on its occurrence in Malaysian seawaters and fish. This study aimed to determine the occurrence of V. parahaemolyticus isolates using polymerase chain reaction targeted at toxin operon gene, thermostable direct hemolysin (tdh), and tdh-related hemolysin genes and to determine antibiotic resistance pattern, genes, and plasmid profile of V. parahaemolyticus from Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Therefore only 10 data articles were qualified by criteria eligibility and included in the meta-analysis, as indicated in Figure 1 and Table 1 . The ten qualified and included articles on Vibrio species-ARG are ( Baron et al., 2016 ; Diep et al., 2015 ; Faja et al., 2019 ; Lepuschitz et al., 2019 ; Letchumanan et al., 2015 ; Rojas et al., 2011 ; Shakerian et al., 2017 ; Shivakumaraswamy et al., 2019 ; Ye et al., 2016 ; Zhang et al., 2018 ). This study revealed the most contaminated environmental samples by pathogen Vibrio species-ARG to include water, prawn, fish, shrimps, clam, molluscs, oysters and mussels with most prevalence distributions of different genes in countries such as China and Malaysia (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore only 10 data articles were qualified by criteria eligibility and included in the meta-analysis, as indicated in Figure 1 and Table 1 . The ten qualified and included articles on Vibrio species-ARG are ( Baron et al., 2016 ; Diep et al., 2015 ; Faja et al., 2019 ; Lepuschitz et al., 2019 ; Letchumanan et al., 2015 ; Rojas et al., 2011 ; Shakerian et al., 2017 ; Shivakumaraswamy et al., 2019 ; Ye et al., 2016 ; Zhang et al., 2018 ). This study revealed the most contaminated environmental samples by pathogen Vibrio species-ARG to include water, prawn, fish, shrimps, clam, molluscs, oysters and mussels with most prevalence distributions of different genes in countries such as China and Malaysia (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…chol tetracycline tet (34) 54 46 85.19 Eastern Austria Lake May' 11- Oct '12 beta-lactam, Ampicillin bla CARB7 54 7 12.96 Beta-lactam bla CARB9 54 2 3.70 Phenicol cat B9 54 3 5.56 sulfonamide and bicyclomycin Bicyclomycin /MATE 54 46 85.19 MATE Multidrug and toxic compound extrusion 54 19 35.19 9 Shivakumaraswamy et al. (2019) Vibrio species tetracycline tet A , tet B , tet C , tet D , tet E , tet G , tet M & tet S 58 45 77.59 India Fish, oyster, clam, olluscs 2011–2014 co-trimoxazole sul genes 38 12 31.58 ampicillin bla TEM 125 8 6.40 cefotaxime bla CTX-M 62 5 8.06 chloramphenicol cat 1 , cat 2 and cml A 15 5 33.33 nalidixic acid qnr A , qnr B or qnr S 71 9 12.68 10 Faja et al. (2019) V .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, plasmid profiling and antimicrobial response studies are common in Vibrio and were widely studied among the cultured shrimps (Molina-Aja et al, 2002). Plasmid-mediated resistance in highly virulent Vibrio parahaemolyticus from marine fish was studied recently by detecting their antibiotic-resistant genes (Faja et al, 2019). They observed that as compared to seawater isolates, higher AMR was observed among the fish Vibrio isolates by showing seventeen antibiotic resistance patterns and the iso- in Salmonella associated with cultured tilapia and catfish were also determined earlier (Budiati et al, 2013).…”
Section: Plasmid Profiling Of Aeromonadsmentioning
confidence: 99%
“…Vibrio parahaemolyticus is an important pathogenic bacterium in both food safety management and mariculture industry (Faja et al., 2019). Rapid and accurate detection technologies of V. parahaemolyticus are essential for effective control of its outbreak and spreading (Kim, Lee, Hwang, & Yoon, 2012).…”
Section: Resultsmentioning
confidence: 99%